Short-Term Effects of Interferential Currents on Chronic Myofascial Pain Syndrome - AKYÜZ, GÜLSEREN DERYA (GALENOS YAYINCILIK, 2013)
Objective: Myofascial pain syndrome (MPS) is a local or regional pain syndrome that causes chronic muscle pain characterized by the presence of trigger points. Standard treatment includes oral medicines, injections, physical therapy modalities and exercises. The aim of this study was to investigate the short-term effects of interferential current, which is a physical treatment modality, on chronic myofascial pain syndrome. Materials and Methods: In this prospective, randomized-controlled study, we included 40 patients with back pain due to chronic myofascial pain syndrome. The patients were divided into two groups. The first group was treated with vacuum and interferential current (VIC) while the second group was given only vacuum treatment (VT). At the same time, range of motion and stretching exercises were suggested as home training. Pain assessment was done at the beginning and on the 15th day of treatment by using a visual analogue scale (VAS) and the disease activity was measured by patients' and physicians' global assessment scale. Mood assessment was performed using the Beck Depression Inventory. Results: The mean age in the VIC and VT groups was 38.2 +/- 13.2 and 48.2 +/- 14.4 years, respectively. There was a statistical difference between before and after treatment VAS scores, and patients' and physicians' global assessment in both groups (p<0.05). Although algometric measurements were statistically significantly improved at the end of the study in group I (p<0.05), those improvements were not observed in group II (p>0.05). The Beck Depression Inventory scores were within normal range in both groups before treatment, however, a significant decrease was found after treatment (p<0.05). Conclusion: Interferential current therapy is an effective treatment method in chronic MPS. When combined with other treatment methods such as exercise, additional benefits may be obtained.
Keywords: Analgesic currents; electrotherapy; interferential currents; myofascial pain; ELECTRICAL NERVE-STIMULATION; MUSCULOSKELETAL PAIN; CURRENT THERAPY; TRIGGER-POINT; MANAGEMENT; DISORDERS; MUSCLE